Anticancer activity of novel oleanolic acid methyl ester derivative in HeLa cervical cancer cells is mediated through apoptosis induction and reactive oxygen species production (Bangladesh Journal of Pharmacology, 2015)
The objective of this study was to determine the anticancer and apoptotic effects of a novel oleanolic acid methyl vanillate derivative in human cervical cancer cells (HeLa). We also evaluated effect of the compound on reactive oxygen species (ROS) generation. MTT and LDH assay were used to evaluate the effect of this compound on HeLa cancer cell cytotoxicity. Confocal microscopy and flow cytometry evaluated the effect on apoptosis induction, while as ROS production was detected by using fluorescent CM-DCFH2-DA. The compound induced potent cytotoxic effects in HeLa cells in a dose-dependent as well as time-dependent manner. The compound also induced characteristic morphological changes indicative of apoptosis. The compound induced both early and late apoptosis in a concentration-dependent and time-dependent manner. The compound led to a significant and concentration dependent increase in the ROS production as the concentration of oleanolic acid methyl vanillate derivative was increased from 0 to 15, 60 and 120 ?M.